Perceived stigma, common mental disorders and associated factors among primary caregivers of adult patients with mental illness attending at public hospitals, Harari regional state, Eastern Ethiopia: A multicenter cross-sectional study - Nigussie, Kabtamu; Tesfaye, Dejene; Bete, Tilahun; Asfaw, Henock (Frontiers in Public Health, 2023)
Background; Caregiving for person with mental distress is a demanding and distressing role, possibly harmful to the care giver's overall quality of life. Numerous studies demonstrate that mental distress and perceived stigma are common among caregivers. However, there is limited study done on this topic in our country. Objective: To determine the magnitude and associated factors of perceived stigma and common mental disorder among primary caregivers of adults with mental illness in public hospitals at Harari regional state, Eastern Ethiopia, April 01 to 30, 2022. Methods: A cross-sectional study design was conducted. A total of 419 participants were recruited by a systematic random sampling technique. The data was collected by using a face-to-face interview and by reviewing patients' charts. Perceived stigma and common mental disorder were assessed by Family Interview Schedule and Self-Reporting Questionnaire respectively. Epidata version 4.6.2 was used to enter data, and SPSS version 20 was used to analyze. Bivariable and multivariable logistic regression were performed. P-values < 0.05 were considered statistically significant. Result: The magnitude of perceived stigma and common mental disorder were 42.5% (95%CI, 37.7-47.3) and 39.4% (95%CI, 34.8-44.0) respectively. Age of caregiver between 26 and 33[AOR=3.13, 95% CI: (1.71-8.93)], no formal education[AOR=3.85, 95% CI: (1.81-8.15)], illness duration ≥7 years[AOR=1.93,95%CI:(1.04-3.57)], family history of mental illness[AOR=1.92, 95% CI: (1.09-3.39)] and poor social support[AOR=4.87, 95% CI: (3.74-12.71)] were significantly associated with perceived stigma. Being female [AOR=1.92, 95% CI: (1.31-3.34)], having no formal education [AOR=4.04, 95% CI: (2.15-10.01)], having a family history of mental illness [AOR=2.26, 95% CI: (1.29-4.00)], having comorbid other illness [AOR=2.13, 95% CI: (1.15-3.94)], and having poor social support [AOR=4.58, 95% CI: (2.53- 8.28)] were significantly associated with common mental disorder. Conclusion: The magnitude of perceived stigma and common mental disorder was high among primary caregivers of patients with mental illness compared with other studies. Age of caregiver between 26-33, no formal education, duration of illness ≥7 years, family history of mental illness and poor social support were associated with perceived stigma and being female, no formal education, family history of mental illness, comorbid other illness and poor social support were associated with common mental disorder.